2007
DOI: 10.1186/1471-2164-8-33
|View full text |Cite
|
Sign up to set email alerts
|

TICdb: a collection of gene-mapped translocation breakpoints in cancer

Abstract: Background: Despite the importance of chromosomal translocations in the initiation and/or progression of cancer, a comprehensive catalog of translocation breakpoints in which these are precisely located on the reference sequence of the human genome is not available at present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 11 publications
0
71
0
Order By: Relevance
“…Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer provides extensive documentation of clinical cases, making possible the estimation of clinical frequencies of translocations. TICdb [5], on the other hand, provides manually curated mapped translocation breakpoints, allowing analysis of the sequences flanking those breakpoints. Several such analyses have been performed over the last years, highlighting the association of various sequence motifs with the presence of double-strand breaks (DSB) in some types of translocations.…”
Section: Introductionmentioning
confidence: 99%
“…Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer provides extensive documentation of clinical cases, making possible the estimation of clinical frequencies of translocations. TICdb [5], on the other hand, provides manually curated mapped translocation breakpoints, allowing analysis of the sequences flanking those breakpoints. Several such analyses have been performed over the last years, highlighting the association of various sequence motifs with the presence of double-strand breaks (DSB) in some types of translocations.…”
Section: Introductionmentioning
confidence: 99%
“…ChimerKB represents a knowledgebase of fusion genes that were compiled from well-known public resources such as GenBank, Mitelman (1), OMIM (15), COSMIC (2), TICdb (4), dbCRID (16) fusion databases and PubMed articles. All entries were manually curated for disease, sequences, breakpoints and experimental evidences.…”
Section: System Design and Methodsmentioning
confidence: 99%
“…A number of databases have been developed to catalogue fusion genes of clinical value. Initial efforts include the Mitelman database (1), COSMIC (2), ChimerDB 1.0 (3) and TICdb (4). …”
Section: Introductionmentioning
confidence: 99%
“…In short, we compiled a database of 548 reported fusion genes. This contained all records in the major public fusion gene databases [4], [17], [18] in addition to fusion genes reported from deep sequencing studies and those found in a thorough literature search. We then designed oligo probes targeting every exon in all of the fusion gene partners, in addition to chimeric exon-exon probes that target every possible exon-exon combination in fusion gene pairs.…”
Section: Methodsmentioning
confidence: 99%